Socioscientific Issues-based Textbook on the Topic of Sustainable Development Goals to Develop Prospective Teachers’ 21st Century Thinking Skills - Desti Herawati*; Rita Istiana (Universitas Syiah Kuala, 2021)
The emergence of the 4.0 industrial revolution requires university graduates to have 21st-century thinking skills that can support them to compete globally. However, the low 21st-century thinking skills of prospective teachers in the group of ways of thinking (critical thinking, problem-solving, and decision making) make the learning process should be able to train and develop these thinking skills. One way to train prospective teachers' 21st-century thinking skills is through the textbooks used in lectures. This study aims to develop textbooks based on socioscientific issues on the topic of Sustainable Development Goals (SDGs). This study used the RD research method with ADDIE design which is composed of 5 stages: Analyze, Design, Develop, Implement, and Evaluate. textbooks were applied at the implementation stage by involving second-semester prospective teachers who contract Environmental Knowledge courses. The instruments used in this study included textbook validation sheets and essay tests. The validation results were analyzed using descriptive analysis, while the essay test results were analyzed using SPSS. The results of the study showed that the socioscientific issues-based textbooks on the SDGs topic received a very good expert assessment and had met the standards of the appropriateness of the content, language, graphics, presentation, and socioscientific issues. Prospective teachers' 21st-century thinking skills in the group of the way of thinking also improved significantly after using socioscientific issues-based textbooks. These indicated that the textbooks which have been developed were effective in practicing the 21st-century thinking skills of prospective teachers.